HUBUNGAN BERAT BADAN LAHIR RISIKO (4000gr) DENGAN ASFIKSIA NEONATORUM DI RSD MAYJEN HM RYACUDU KOTABUMI LAMPUNG UTARA - Elfira Awalia Rahmawati; yuli lestari; Ida Subardiah Pelitawati (Universitas Mitra Indonesia, 2020)
WHO (World Health Organization) reports that neonatorum asphyxia deaths in Indonesia amounted to 29.9% reported to occur on the first life, and 75.6% on the week after birth. In Lampung, there were 47 events per 1000 in 2017. The purpose of this research was to fine the relationship of Birth Weight with the Asphyxia in Neonaturum. The research method uses descriptive analytic design, with cross sectional approach. The population was all neonatus in 2017 in the neonate room and VK in HM Ryacudu Mayjend Kotabumi, North Lampung Hospital were 820 babies. 269 samples were taken by random sampling technique. The results obtained pvalue 0.003 means pvalue α, it is concluded there is a relationship between birt weight with asphyxia. An OR value of 2.2, which means neonates born with birth weight (2500 grams and 4000 grams) have a 2.2-fold potential to occur asphyxia neonaturum compared to unweighted birth weight. Asphyxia neonatorum can be avoided by maintaining the weight of the baby during normal wombs, so mothers are expected to have their health checked routinely during pregnancy.